Controle adaptativo de corrente média ponderada em conversores com filtro de saída do tipo LCL - Plotzki, Haiglan Frank Batista (Universidade Federal do Pampa, 2015)
Using electronic power converters has many applications like as drive motors, connection to the distribution grid etc. The most suitable converter for each case depends on the desired application. The most common topologies for the converters are buck, boost and the full-bridge converter. In all cases it is used the actuation of electronic switches (MOSFET, IGBT and Thyristor) for synthesizing a desired waveform. A consequence effect of switching these devices is setting up high-frequency harmonic components at the converter output. To reduce this effect, filters are used to deny the passage of waveforms that have high frequency and allow the passage of waveforms that have low frequency. The signal generated by the converter is chosen so that the system connected to it presents the desired behavior, thereby controllers are used to perform the adjustment of the voltage generated. In this work the Adaptive Control by Reference Model is used to track the weighted average current of the inductors from the LCL filter connected to an electronic power converter with full-bridge configuration. To verify the controller, simulations were performed in Simulink software and in a bench for testing designed for this purpose. The results of both simulations show that the proposed controller performed the tracking of the reference used. However, the experimental results presented problems related to instrumentation for measuring the circulating currents on the filter inductances, as well as problems related to the inverter drive.
Keywords: Electrical engineering; Adaptive control; Electronic Converters; Engenharia elétrica; Controle adaptativo; Conversores eletrônicos; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA